Information and Communication Technology skills for Effective Competence Based Curriculum Implementation in Kenya - Ndiritu, Anne; Gatotoh, Augustine (Advances in Social Sciences Research Journal, 2020)
The vision of education service delivery in Kenya is to have an internationally competitive quality education, training and research for sustainable development. More developed countries are associated with their great investment in human capital. They are also associated with development of ICT which has led to improved standards of living and good governance. This study was carried out on 395 pre-school teachers who were undertaking their in-service training in Kiambu County. The study sort to establish ICT whether the teachers engaged in ECD centers had any skills in ICT. This study further sort to establish whether there was integration of ICT in teaching and learning in selected preschools in Kenya. A researcher designed questionnaire was used in the study. A total of 60.83 % of the total population had no knowledge of ICT and therefore did not integrate ICT in their teaching and learning in the selected preschools. All the teachers expressed that the government had not sponsored them for ICT training and the little they had they had sponsored themselves. Grounded on these findings the study recommended that the government should be on the forefront to not only invest in ICT infrastructure but also in education of teachers in ICT. With the paradigm shift in the Kenya’s education curriculum this concern should be immediate. The government should take up the responsibility of ensuring that all teachers are exposed to ICT skills since these will change their interaction with the students who are quite ahead of their teachers in technology.